Bone-conducted ultrasonic auditory brainstem response thresholds in a mouse model of cisplatin-induced hearing loss - Akihito Nakanishi; Noriko Nagase; Hirokazu Kousaki; Bakushi Ogawa; Kazuhiro Horii; Iori Niitsu Morimoto; Yuka Morita; Fumiaki Nin (PLoS ONE, 2026)
Cisplatin is widely used in cancer treatment but can cause hearing loss, predominantly at high frequencies. Auditory responses to bone-conducted ultrasonic stimulation have been proposed as a potential indicator of cochlear function, but it remains unclear how such responses are affected by cochlear damage. In this study, we measured auditory brainstem response (ABR) thresholds within and beyond the conventional hearing range in a mouse model of cisplatin-induced hearing loss. Of 32 mice initially examined, 9 were excluded at baseline because of pre-existing high-frequency hearing impairment. The remaining animals received either saline or cisplatin, and post-treatment analysis in the cisplatin group was based on 16 surviving mice. Cisplatin administration increased ABR thresholds within the conventional hearing range. In contrast, threshold shifts evoked by bone-conducted ultrasonic stimulation were often smaller. Paired comparison of mean threshold shifts showed that changes evoked by bone-conducted ultrasonic stimulation were significantly smaller than those within the conventional hearing range. These findings show that ABR threshold shifts evoked by bone-conducted ultrasonic stimulation do not necessarily parallel those within the conventional hearing range in cisplatin-treated mice.